EVALUATION OF INVESTMENT PROJECTS IN CASE OF CONFLICT BETWEEN THE INTERNAL RATE OF RETURN AND THE NET PRESENT VALUE METHODS - Mackevičius, Jonas; Tomaševič, Vladislav (Ekonomika, 2010)
Results obtained by employing the net present value (NPV) and the internal rate of return (IRR) methods allow to objectively determine the effectiveness and attractiveness of an investment project and to compare investment projects differing in scope, length or the amount of expected profit. While results obtained by the NPV and IRR methods normally correlate, contradictions are possible in individual cases. Such contradictions are called ‘conflict between the IRR and NPV methods’. The paper deals with the main characteristics of NPV and IRR, analysing the substance of the conflict and cases of its manifestation. A technique for the resolution of the NPV and IRR conflict is proposed.